Komputasi Paralel GPU Dengan Teknologi Nvdia Cuda Untuk Enkripsi Berkas Pdf Menggunakan Algoritma RC4 DAN MD5 - Al Farissi; Samatra Marwa Hany; Rifkie Primartha (Universitas Sriwijaya, 2017)
AbstractOne way to secure files on storage media is by cryptographic techniques.The content of PDF files sometimes Contains with important information. therefore information security becomes a priority at this time. In this research, PDF files will be encrypted with MD5-RC4 technique. This combination makes information more secure and protected from information disclosure. This research implement parallel computing using GPU and CPU that make a performance of process run faster. When Nvidia released CUDA, GPU Become a strong power as an efficient accelerator for complex computations. Therefore, the GPU with CUDA and the comparision between CUDA and CPU will be discussed in this study.Keywords: PDF, Enkripsi,CUDA,MD5,RC4.